Pengaruh APGAR Family Terhadap Quality of Life Pasien Diabetes Mellitus Tipe 2 - Feny Tunjungsari; Isbandiyah; Farajihan (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2020)
Introduction: Indonesia was a country from 10 countries that possesses the most dm prevalence of diabetes mellitus(DM) in urban areas amounting to 5.7 %. According to data center and health of the republic of indonesia, that theproportion of diabetes mellitus in the city of malang 2,3 %. The high number of diabetes mellitus in the city ofmalang is because the lack of the application of the family function well in people with DM type 2. Obstacles arisingthat is the majority of the community ignore this metabolic types of disease so that it cannot be detected earlier .Therole of family in aim diabetics mellitus type 2 believed to have the effect on the quality of life of sufferers DM. Aim ofstudy: This study aimed toanalyze function offamilies according to familyAPGAR to quality of life dm patients type2. Method: this study used an observational analytic with cross the sectional approach, 95 subjects were werechosen by simple random sampling. Data was analyzed using Spearman test. Results and Discussions: the resultsshowed a value of significance APGAR against quality of life as much as 0.000, which means there were asignificant relation exists (p < 0.05). A correlation coefficient APGAR against quality of life as much as 0.93, whichmeans of the nature of the strength of the relations is very strong. Conclusions: It can be concluded that there is avery strong influence (0.000) between APGAR family against quality of life the patient DMtype 2.